Meckel's Diverticulum-Induced Intussusception Coinciding with Diabetes Mellitus in a Young Adult Male: A Rare Case Study - Digambiro, Reza Aditya; Parwanto, Edy; Setianingrum, Dyah Ayu Woro; Ilona, Florinda; Lestari, Indah Widya; Chendrasari, Julian (Jurnal Kedokteran Meditek, 2025)
Introduction: Intussusception in adults, especially when caused by Meckel's Diverticulum, is a rare occurrence, often presenting with nonspecific symptoms such as abdominal pain and nausea, making it challenging to diagnose. When concurrent with conditions like diabetes mellitus, the situation need particular care. Case Illustration: A 27-year-old male with a medical history of diabetes presented with severe right abdominal pain, nausea, and a reduced appetite. Initial symptomatic treatment did not alleviate the condition. Subsequent CT scans revealed an ileo-ileal intussusception triggered by Meckel's Diverticulum and partial high obstruction ileus, leading to surgical intervention. Discussion: Ileo-ileal resection (end to end anastomosis) and adhesiolysis surgery were successfully performed, followed by vigilant postoperative monitoring for complications, effective pain management, maintenance of drain patency, and careful glucose level monitoring. The patient's significant postoperative improvement underscores the importance of early diagnosis and timely surgical intervention in managing Meckel's Diverticulum-induced intussusception in adults. Conclusion: The clinical course also highlighted the importance of tailoring postoperative care considering the patient's comorbidities, in this case, diabetes mellitus. This case served as a reminder for clinicians to consider Meckel's Diverticulum as a potential cause of intussusception in adults presenting with abdominal pain.